Web-basert bildelyd-mentoring - Pedagogiske muligheter og utfordringer - Birgitte Wergeland; Petter Mathisen (Universitetsforlaget, 2009)
The purpose of this article is threefold. First, it reviews the literature on mentoring as a modern form of individually enhanced competency development. Second, it describes what characterizes mentor conversations conducted in the form of web-based video communication and establishes the concept of Web-based video mentoring (WVM). Third, based on a case study, the article highlights and discusses pedagogical challenges and possibilities that emerge using WVM. Moreover the article discusses the relationship between trust and technical competency, and argues for the importance of picture and sound in the mentor relationship and in the designing of the conversations. Finally the case study illustrates how form, process and leadership are decisive factors and that continuity through accessibility is of importance for a successful Web-based video mentoring.